Self-Management Education pada Pasien Diabetes Melitus - Etlidawati, Etlidawati; Romdhoni, Muhammad Fadhol; Yulistika, Diyah; Linggardini, Kris (Faletehan Health Journal, 2024)
Diabetes self-management education (DSME) integrates four aspects of diabetes management with an emphasis on behavioral interventions that assist individuals with diabetes in adopting lifestyle changes for their self-care from the desease. DSME encompasses diets, exercises, treatments, and exercise schedules for patients with diabetes, aiming to enhance patients' ability to self-care. This study aimed to assess the effects of DSME on the self-care of patients with diabetes by using a booklet medium at Purwokerto Islamic Hospital. This quantitative research employed a quasi experimental design with a control group pre-post test design and gave a booklet media to the intervention group. This research involved 32 randomly selected respondents who were divided into control and intervention group. The statistical analysis used an independent t-test and showed a significant difference in the care of patients with diabetes (p=0.00<0.05) between the two groups. Following DSME intervention, 75% respondents in the intervention group exhibited a good self-care behavior; meanwhile, the control group was just 56%. The statistical analysis showed a difference in the self-care mean of the intervention group, which improved meaningfully (p-value 0.01); however, the control group was unmeaningful (p-value 0.06). This research showed DSME is able to improve the self-care of patients with diabetes mellitus.